Corporate Social Responsibility of Commercial Banks in Nepal: Expectation or Dilemmas - Bista, Raghu Bir (Journal of Development and Administrative Studies, 2020)
This study examines the practices and dilemmas of the corporate sectors to CSR in Nepal. Using explorative and descriptive methods, the study analyzes secondary and primary combo data sets covering only the financial sector, particularly private commercial banks to unlock CSR issues of the corporate sectors. As a result, the study finds a positive perception, higher awareness level and good adoption of the private commercial banks on CSR. In practice, the study gets CSR as voluntary social responsibility in almost all private commercial banks. Similarly, the study finds the least CSR size. Its flow is discrete and irregular without priority. Lastly, the satisfaction level of almost all stakeholders is poor and says that it should be obligatory to banks for encouraging implications. Since CSR practices is a dilemma to the corporate sector and the government in the imperfect open market in developing countries like Nepal, the government should come beyond the policy frameworks of CSR to transform voluntarily CSR to mandatory CSR in the practices. Furthermore, the government should improve the monitoring and evaluation system for CSR to make mandatory additional resource mobilization for social causes for improving social welfare and socio-economic justice in society for reducing have and have-not gaps.